2015
DOI: 10.1111/bcp.12588
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based pharmacokinetic model for 6‐mercpatopurine: exploring the role of genetic polymorphism in TPMT enzyme activity

Abstract: AIMSTo extend the physiologically based pharmacokinetic (PBPK) model developed for 6-mercaptopurine to account for intracellular metabolism and to explore the role of genetic polymorphism in the TPMT enzyme on the pharmacokinetics of 6-mercaptopurine. METHODSThe developed PBPK model was extended for 6-mercaptopurine to account for intracellular metabolism and genetic polymorphism in TPMT activity. System and drug specific parameters were obtained from the literature or estimated using plasma or intracellular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition to differences in biotransformation, other pharmacokinetic factors, influenced by age, may contribute to the requirement for higher azathioprine doses described by our study, such as changes in absorption and bioavailability (5,31). TPMT activity might have been affected by concomitant mesalazine treatment (32); however, frequency of patients in therapy with mesalazine was not significantly different between cases and controls.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to differences in biotransformation, other pharmacokinetic factors, influenced by age, may contribute to the requirement for higher azathioprine doses described by our study, such as changes in absorption and bioavailability (5,31). TPMT activity might have been affected by concomitant mesalazine treatment (32); however, frequency of patients in therapy with mesalazine was not significantly different between cases and controls.…”
Section: Discussionmentioning
confidence: 71%
“…It also has been reported that 6-MP has a narrow therapeutic index with a corresponding potential drug-related toxicity in Caucasian populations. 21 Excess accumulation of 6-MMPN and 6-TGN has been shown to induce leukopenia and hepatotoxicity by inhibiting nucleosides and protein synthesis; however, such data for Chinese population are sparse. For such a reason, we sought to evaluate measures of correlation between 6-MP metabolite concentrations and thiopurine-induced adverse effects in Chinese paediatric patients afflicted by ALL.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard a useful mechanistic modeling tool that can be applied to accomplish this objective involves physiologically based pharmacokinetic (PBPK) modeling and simulation, which provides a quantitative framework to assess potential DDI . In addition, recent advances in PBPK modeling and simulation have enabled this approach to be used as a mechanistic modeling tool for the evaluation of the possible impact of various intrinsic and extrinsic factors affecting the pharmacokinetics of drugs such as drug‐disease interactions in organ impairment patients, pharmacogenetics, drug formulation, and pediatrics …”
mentioning
confidence: 99%